Gladstone's Influence in America Reactions in the Press to Modern Religion and Politics - Peterson, Stephen J. (Springer International Publishing, 2018)
By the end of the nineteenth century, William Gladstone was arguably the most popular statesman in America since Lincoln. How did a British prime minister achieve such fame in an era of troubled Anglo-American relations? And what do press reactions to Gladstone's policies and published writings reveal about American society? Tracing Gladstone's growing fame in the United States, beginning with his first term as prime minister in 1868 until his death in 1898, this volume focuses on periodicals of the era to illuminate how Americans responded to modern influences in religion and politics. His forays into religious controversy highlight the extent to which faith influenced the American cult of Gladstone. Coverage of Gladstone's involvement in issues such as church disestablishment, papal infallibility, Christian orthodoxy, atheism and agnosticism, faith and science, and liberal theology reveal deepening religious and cultural rifts in American society. Gladstone's Influence in America offers the most comprehensive picture to date of the statesman's reputation in the United States.